Peran Mahasiswa dalam Pengembangan Agromedicine melalui Promosi Kesehatan Untuk Meningkatkan Mutu Kesehatan Di Indonesia - Putu Devie Sri Astari (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2020)
ABSTRACTBackground: Health problems in Indonesia are caused by Non-Communicable Diseases (PTM). Degenerative disease is one of the most common problems and is related to antibiotic resistance. The development of agromedicine is very potential in Indonesia because it has the fourth largest bioverity in the world and abundant natural resources. Consumption of herbal medicine as traditional medicine has an effect on healing degenerative diseases. Herbal medicines are sourced from medicinal plants as a medical identity in Indonesia in terms of developing agromedicine.Discussion: The use of traditional Indonesian medicines has become a national culture because Indonesia is a mega-center of medicinal plants in the world. Development ofagromedicine in the field of herbal medicines requires contributions from various related parties including students, media service providers, the government, producers and research institutions. Health promotion method is a form of information delivery that aims to change people's behavior through the active role of students as agents of change.Conclusion: Optimizing the use of agromedicine is needed to meet the needs of high-quality national medicines. All parties make a major contribution in achieving the goals. Students as agents of change can do health promotion to the community so as to realize prosperity by utilizing natural resources available in Indonesia.